A dendroclimatological approach to diameter growth in adult cork-oak trees under production - Costa, A.; Pereira, H.; Oliveira, A. (Trees, 2001)
The diameter growth of mature cork oaks under cork production in southwestern Portugal was studied during a 9-year cork-production cycle in relation to fluctuations in precipitation and temperature, and to drought indices combining the two variables. A dendroclimatological approach was applied to the series of 8 complete years contained in the cork-production cycle and growth effects were removed by standardization and calculation of annual growth indices. The most important factor positively influencing diameter growth was cumulative precipitation in the growing season (January–June) and in the previous autumn and winter (October/November of the previous year–June). The monthly temperature is a less influential factor, negatively correlated with diameter growth in high summer drought (August) and positively correlated at the beginning of physiological activity (March).
Keywords: climatic fluctuations; dendroclimatology; diameter growth; Mediterranean climate; Quercus suber L.